Sustainable energy-efficient conversion of waste tea leaves to reducing sugar: optimization and life-cycle environmental impact assessment - Chakraborty, Rajat; Roy, Oindrila (Journal of Environmental Engineering and Landscape Management, 2022)
Innovative protocols involving energy-proficient pretreatment of waste tea leaves (WTL) for preparation of cellulose and its subsequent photocatalytic hydrolysis (PH) for production of total reducing sugar (TRS) have been reported. The WTL was subjected to alkali pretreatment (60 °C, 1 h) followed by bleaching (employing peracetic acid, 65 °C, 2 h) in a quartz halogen irradiated batch reactor (QHIBR) for efficient separations of lignin and hemicellulose fractions to produce WTL derived cellulose fiber (WTLDCF; 94.5% cellulose). Consequent PH of WTLDCF in QHIBR using combination of Amberlyst-15 and nano-TiO2 catalysts was optimized (parameters: 40 min, 70 °C, 1:30 WTLDCF to water weight ratio and 5 wt. % catalyst concentration) employing Taguchi design that provided maximum 68.25% TRS yield. The QHIBR demonstrated faster hydrolysis and superior energy-efficiency over conventional reactor owing to quartz halogen irradiation. Life cycle assessment indicated an acceptable global warming potential of 2.215 kg CO2 equivalent; thus, establishing an energy-efficient environmentally sustainable WTL valorization process.